Religious Power as a Form of Political Power - Żyromski, Marek (Univerzita Pardubice, 2007)
The question of power is one of the most difficult and complex phenomena to analyze. The question of power is not only a complex one, but the notion itself is a multidimensional phenomenon. Michael Mann introduced IEMP model of power - four sources of social power – ideological, economic, military and political. They fundamentally determine the structure of societies. As a form of ideological power can be viewed religious power. Religious power can be analyzed as a form of ideological power or as a form of political power.
Keywords: religious power; social power; IEMP model; Roman Empire